PAM-4 and Duobinary Direct Modulation of a Hybrid InP/SOI DFB Laser for 40 Gb/s Transmission over 2 km Single Mode Fiber - Abbasi, A.; Spatharakis, C.; Kanakis, G.; André, N. S.; Louchet, H.; Katumba, A.; Verbist, J.; Yin, X.; Bauwelinck, J.; Avramopoulos, H.; Roelkens, G.; Morthier, G. (In Optical Fiber Communication Conference, 2016)
We demonstrate 40 Gb/s PAM-4 and Duobinary direct modulation of a heterogeneously integrated InP on SOI DFB laser. Transmission measurement was performed using a 2 km NZ-DSF with a PRBS 215 and 1.5 Vpp swing voltage.